Knock-In Mice with Myo3a Y137C Mutation Displayed Progressive Hearing Loss and Hair Cell Degeneration in the Inner Ear - Peipei Li; Zongzhuang Wen; Guangkai Zhang; Aizhen Zhang; Xiaolong Fu; Jiangang Gao (Neural Plasticity)
Myo3a is expressed in cochlear hair cells and retinal cells and is responsible for human recessive hereditary nonsyndromic deafness (DFNB30). To investigate the mechanism of DFNB30-type deafness, we established a mouse model of Myo3a kinase domain Y137C mutation by using CRISPR/Cas9 system. No difference in hearing between 2-month-old Myo3a mutant mice and wild-type mice was observed. The hearing threshold of the ≥6-month-old mutant mice was significantly elevated compared with that of the wild-type mice. We observed degeneration in the inner ear hair cells of 6-month-old Myo3a mutant mice, and the degeneration became more severe at the age of 12 months. We also found structural abnormality in the cochlear hair cell stereocilia. Our results showed that Myo3a is essential for normal hearing by maintaining the intact structure of hair cell stereocilia, and the kinase domain plays a critical role in the normal functions of Myo3a. This mouse line is an excellent model for studying DFNB30-type deafness in humans.